Statistical analysis of characteristics of radioactive aerosol in the ventilation system "Bypass" of object "Ukryttya" during the period of 2003–2012 years - Y. V. Khomutinin; V. P. Protsak; V. Y. Khan; B. I. Ogorodnikov (Ядерна фізика та енергетика)
Results of the statistical analysis of dynamics of parameters of a radioactive aerosol in ventilating Bypass system during 2003 - 2012 have been presented. For volume concentration of aerosol carriers of activity 137Cs, 241Am and sums of -emitting nuclide the distinct exponential global trends were established. Quantitative esti-mates of seasonal trend component of characteristics of radioactive aerosol in the "Bypass" were received.